(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Scabies is a common cause of itching is produced by infestation with the mite Sarcoptesscabiei var hominis. Poor hygienic condition and overcrowding, permitting close body contact favour thetransmission of the disease. Scabies is more prevalent in overcrowded communities with low socioeconomicconditions. The point prevalence in the general population of rural India is about 13%,In Maharashtra81% of inmates of an orphanage in rural area,[6] 72% of cases are seen in the age group of School goingchildren’s. Pama Kushtha characterized by many small Pitikas, Srava, Kandu, Toda and Daha that may beconsidered as scabies in contemporary science. Aim: The present study is aimed at evaluating the effect ofVachadi Ointment in the management of Pama Kushta. Material & Methods: The present study is designedas a Non-randomized controlled clinical study, in which minimum of 30 patients will be enrolled. VachadiOintment will be administered external application 2-3 times in a day. Assessment will be recorded on 3rd,5th, 7th and 14th days. Results: Changes will be observed in subjective parameters such as Kandu (Itching),Toda (Pain), Daha (Burning) and objective parameters such as Pitika (Eruption) and Srava (Discharge).Conclusion: Suitable conclusion will be drawn post completion of the trial.